Ectopic over-expression of BoHO1, a cabbage heme oxygenase gene, improved salt tolerance in Arabidopsis A case study on proteomic analysis - Duan, Xingliang (Journal of plant physiology, 2016)
Copyright © 2016 Elsevier GmbH. All rights reserved.